The impact of training on some distressed middle-functional variables according to the dynamic rhythm Bdorth physical - Abedulsattar, Muna (Journal of Physical Education, 2007)
The physiological variables which by measured accurately by medical equipment or lab analyses are considerd as important indicators for those who are doing the training process by making or revising thir traning methods with that is suitable with performance aims and requirements in the ervious athletics games . The scientific experiments have proved that the biorhythm with its various cycles have a certain and clear impact on the various sides of anthletic performance . the refor its is necessary for the coach to take in to consideration the various biorhythm cycles between its negative and positive phases . The problem of the nesearch is that most of coaches do not attribute the reasons of differences between the blood comporents and som physiologyical variables to the effect of the research is to be acquainted with some of the boold components befor and after the physical straim in the negative and positive phases of the physical cycle of athletics and non-athletics. The assumptions have organized that there are differencse with statistical indication in som boold componets befor and after strain in the negative and positive phases for the physical sycle of the athletics and non- athletics . The sample of the research consists of ( 10 ) athletics and ( 10 ) non – athletics students from the college of physical education . It has been reached to that there are sensible differences among the physiological variables for the athletics during the negative phase of the physical cycle . It also has been reached to that the rates of these variables are `faster decrasing in the athletics that in the non – athletics because of the boold cycle activity inside the muscle , thus the compensation processes will be faster . The research recommends of doing research like this one upon another variables and their impants on other biorhythm cycles